2018
DOI: 10.3126/jnps.v37i2.17081
|View full text |Cite
|
Sign up to set email alerts
|

Junk Food Consumption Among Secondary Level Students, Chitwan

Abstract: Introduction: Junk food is a pejorative term for cheap food containing high levels of calories from sugar or fat with little fibre, protein, vitamins or minerals. This study was conducted to assess the junk food consumption and patterns of consumed junk food among secondary level students.Material and Methods: This was a descriptive cross-sectional research. Hundred forty-two respondents were drawn by using cluster sampling method. Self-administered semi-structured questionnaire in Nepali Version was used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 4 publications
3
31
0
Order By: Relevance
“…The school snacks consumed by most of the students were unhealthy as they consumed commercially prepared junk foods bought either from the school's tuck shop, nearby vending shops or purchased deep-oil-fried foods from the canteen. This finding is corroborated by the studies conducted in Kathmandu, 16,17 Lalitpur, 25 Chitwan, 21 and Parsa 26 districts of Nepal. The finding is also comparable to a study conducted in the Himanchal 27 and the Maharastra provinces of India 28 and a study conducted in China.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The school snacks consumed by most of the students were unhealthy as they consumed commercially prepared junk foods bought either from the school's tuck shop, nearby vending shops or purchased deep-oil-fried foods from the canteen. This finding is corroborated by the studies conducted in Kathmandu, 16,17 Lalitpur, 25 Chitwan, 21 and Parsa 26 districts of Nepal. The finding is also comparable to a study conducted in the Himanchal 27 and the Maharastra provinces of India 28 and a study conducted in China.…”
Section: Discussionsupporting
confidence: 73%
“…15,16 A growing body of literature reveals that consuming commercially processed instant foods and beverages, which are widely known as junk foods, have become common place among school children in both the urban and rural areas of Nepal. [16][17][18][19][20] A cross-sectional study conducted in Chitwan, indicates that snacking on junk foods was common among the secondary level students, 21 yet further evidence is needed to fill the knowledge gap on snacking behavior among the school children at the basic education level.…”
Section: Introductionmentioning
confidence: 99%
“…5 Of them, 54.2%, over half of the adolescents have low knowledge of proper food and its consequences; thus, the majority of them were at risk of eating junk food. 6 In addition, the consumption of junk food varied by age; it was found that the higher proportion of junk food was in early adolescents (93%) as compared to late adolescents (89%). 7 This difference in the consumption of junk food is determined by the taste and availability and by home and environmental factors.…”
Section: Introductionmentioning
confidence: 98%
“…Almost one-fourth of the total population is comprised of adolescents [26]. Of them, 54.2%, over half of adolescents have low knowledge of proper food and its consequences; thus, the majority of them were at risk of eating of junk food [27]. In addition, the consumption of junk food varied by age; it was found that the higher proportion of junk food was in early adolescents (93%) as compared to late adolescents (89%) [28].…”
Section: Introductionmentioning
confidence: 99%